Comparison of a Cost-Effective Integrated Plankton Sampling and Imaging Instrument with Traditional Systems for Mesozooplankton Sampling in the Celtic Sea - Pitois, Sophie G.; Tilbury, Julian; Bouch, Paul; Close, Hayden; Barnett, Samantha; Culverhouse, Phil F. (Frontiers in Marine Science, 2018)
Three plankton collection methods were used to gather plankton samples in the Celtic Sea in October 2016. The Plankton Image Analysis (PIA) system is a high-speed colour line scan-based imaging instrument, which continuously pumps water, takes images of the passing particles, and identifies the zooplankton organisms present. We compared and evaluated the performance of the PIA against the Continuous Automatic Litter and Plankton Sampler (CALPS) and the traditional ring net vertical haul. The PIA underestimated species abundance compared to the CALPS and ring net and gave an image of the zooplankton community structure that was different from the other two devices. There was, however, good agreement in the spatial distribution of abundances across the three systems. Our study suggests that the image capture and analysis step rather than the sampling method was responsible for the discrepancies noted between the PIA and the other two datasets. The two most important issues appeared to be differences in sub-sampling between the PIA system and the other two devices, and blurring of specimen features due to limited PIA optical depth of field. A particular advantage of the CALPS over more traditional vertical sampling methods is that it can be integrated within existing multidisciplinary surveys at little extra cost without requiring additional survey time. The biggest advantage of using the PIA, in addition to those associated with using the CALPS, is that it removes the need to collect physical preserved samples for subsequent analysis in the laboratory. Provided a taxonomist is present on-board, the system in its current form can also integrate the sampling and analysis steps, thus increasing the speed, and cutting down substantially on the cost, of obtaining zooplankton information. Another clear advantage is that the images are available in near real-time. Once the noted issues have been dealt with, a revised PIA system will have the potential to become an important element of an integrated monitoring program, for the measurement of zooplankton.